Pengaruh Konsentrasi Air Kelapa Dan Lama Perendaman Stek Terhadap Hasil Tanaman Tomat (Solanum lycopersicum) - Febriyanti (Indoensia), Siti Eka; Susilowati (Indoensia), Yulia Eko; Iftitah (Indoensia), Siti Nurul (JURNAL VIGOR, 2024)
ABSTRACTTomatoes is one type of fruit vegetables annuals that may be planted in the lowlands and high. The coconut water as a natural growth regulator by concentration of the certain and long immersion could increase yield of tomatoes. Research on the influence the coconut water and long immersion cuttings of the results of tomato plants have been conducted by 2022 on 14 July until 20 September 2022. Research carried out in Bojong Hamlet, Maduretno Village, Kaliangkrik District, Magelang Regency with an altitude place 763 m above sea level. Research methodology used experiment factorials ( 4x3 ) arranged in the complete random design ( rakl ) two factors in treatment by three as a block. The first factor was the concentration of coconut water, namely 25%, 50%, 75% and 100%. The second factor was long immersion cuttings, namely 4 hours, 8 hours and 12 hours. Date were analyzed using variance and tested using orthogonal polynomials. The concentration of 25% coconut water gave the fastest age of flowering and the concentration of 100% coconut water produced the largest volume of fruit. Long immersion cuttings offer the same result height of plant, age of flowering, number of fruit per plant, weight of fruit per plant, volume of fruit and percentage of plants attacked by the virus. The concentration and long immersion cuttings gave a same result to the all parameters observation.Keywords: coconut water, concentration, long immersion, tomato.